35.9k views
1 vote
For f(x)=2x + 1 and g(x)= x^2 - 7, find (f + g)(x)

User DangerDave
by
5.4k points

2 Answers

0 votes
the answer to the question
For f(x)=2x + 1 and g(x)= x^2 - 7, find (f + g)(x)-example-1
User Questionable
by
4.9k points
3 votes

Answer:

(f + g)(x) = x² + 2x - 6

Explanation:

We have (f + g)(x) = f(x) + g(x)

f(x) = 2x + 1 and g(x) = x² - 7

Substituting

(f + g)(x) = f(x) + g(x) = 2x + 1 + x² - 7 = x² + 2x +1 -7

(f + g)(x) = x² + 2x - 6

So we have

(f + g)(x) = x² + 2x - 6

User Woxxy
by
5.4k points